Penerapan Pendekatan Matematika Realistik Pada Materi Himpunan untuk Siswa SMP/MTS - Nasution, Afifah Nabila; Arifin, Cyntia Suarni; Sastika, Weni (Universitas Muhammadiyah Enrekang, 2024)
This study aims to find out and describe how the application of a realistic mathematical approach to set material for SMP/MTS students. The research method used is a literature review. The stages of the literature review are article collection, article reduction, article display, organizing and discussing, and drawing conclusions. The articles used in this study were 20 out of 28 articles obtained from Google Schooler. Based on this research, it was found that the application of a realistic mathematical approach to set material is very suitable to be applied because it is more effective and valid so that the responses received by students are also positive and can improve mathematics learning outcomes for SMP/MTS students, especially in set material.